Strategi Pengelolaan Instagram @Sukabumitoday sebagai Media Informasi Kota Sukabumi selama Masa Pandemi Covid-19 - Papanda, Helen Tri; Rusdi, Farid (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Sukabumi City is the smallest city in West Java Province, with the potential for nature tourism and natural resources that are well known to the public. However, the Sukabumi City government's attention to the area is still lacking and makes this potential invisible. The government is less focused on developing information media for the City of Sukabumi. A digital-based media company, INFOSMI, is an independent community on social media that aims to provide information in the form of news and tourist attractions in Sukabumi City. This community has an Instagram account, @sukabumitoday. It is known that the communication strategy carried out by the @sukabumitoday Instagram account goes through 7 stages. The primary strategy on Instagram @sukabumitoday is to upload photos and videos sent from Instagram followers @sukabumitoday and provide exciting photo captions so that the content and messages to be conveyed become informative and persuasive. The Instagram account @sukabumitoday also takes advantage of the features that exist on Instagram to maximize its function as a medium of information for the City of Sukabumi. The @sukabumitoday account uses messages with encouragement and jokes so that all information can be adequately conveyed. Kota Sukabumi merupakan kota terkecil di Provinsi Jawa Barat dengan potensi wisata alam dan kekayaan alam yang sudah banyak dikenal masyarakat. Namun, perhatian pemerintah Kota Sukabumi terhadap daerahnya masih kurang dan membuat potensi tersebut tidak terlihat. Pemerintah kurang fokus untuk mengembangkan media informasi Kota Sukabumi. Sebuah perusahaan media berbasis digital, INFOSMI, merupakan komunitas mandiri di media sosial yang bertujuan memberi informasi berupa berita dan tempat wisata yang ada di Kota Sukabumi. Komunitas ini memiliki akun Instagram @sukabumitoday. Diketahui jika strategi komunikasi yang dilakukan oleh akun instagram @sukabumitoday melewati 7 tahapan. Strategi utama pada Instagram @sukabumitoday adalah mengunggah foto-foto dan video kiriman dari pengikut Instagram @sukabumitoday, memberikan keterangan foto yang menarik agar isi serta pesan yang ingin disampaikan menjadi informatif dan persuasif. Akun Instagram @sukabumitoday juga memanfaatkan fitur-fitur yang ada pada Instagram sehingga memaksimalkan fungsinya sebagai media informasi untuk Kota Sukabumi. Akun @sukabumitoday menggunakan pesan dengan dorongan dan candaan, agar semua informasi dapat tersampaikan dengan baik.